2007
DOI: 10.1055/s-2007-963339
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcystein verbessert die lysosomale Funktion und beschleunigt den Abbau von Photorezeptoraußensegmenten in der RPE-Zellkultur

Abstract: In our cell culture model of ROS fed RPE cells simulating aged RPE ACC improves lysosomal volume and metabolism. Therefore ACC may represent a new prophylactic and causal treatment option for AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
(25 reference statements)
0
2
0
1
Order By: Relevance
“…Therefore, limiting RPE oxidative stress may represent an effective way to slow or possibly reverse vision loss of patients due to diseases such as AMD. Indeed, several in vitro studies have shown that oxidative stress-related RPE cell death and dysfunction was improved when the cells were treated with antioxidants [73], [74], [75], [76]. Furthermore, a significant reduction toward retinal degeneration was reported in clinical trials involving AMD patients ingesting antioxidants such as lutein, zeaxanthin, zinc, vitamin C, and vitamin E [77], [78].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, limiting RPE oxidative stress may represent an effective way to slow or possibly reverse vision loss of patients due to diseases such as AMD. Indeed, several in vitro studies have shown that oxidative stress-related RPE cell death and dysfunction was improved when the cells were treated with antioxidants [73], [74], [75], [76]. Furthermore, a significant reduction toward retinal degeneration was reported in clinical trials involving AMD patients ingesting antioxidants such as lutein, zeaxanthin, zinc, vitamin C, and vitamin E [77], [78].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, pioneering proteomic profiling studies revealed the protein expressions in human RPE [21], drusen [22] and lipofuscin [23]. Other studies compared native differentiated to cultured dedifferentiated RPE cells [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Aufgrund dieses Wirkungsmechanismus wird Glutathion als Antioxidans zur Nahrungsergänzung genutzt. In der RPE-Zellkultur konnte man durch Zusatz von N-Acetylcystein das lysosomale Volumen und die korrespondierende Funktion deutlich verbessern [54]. Am Tiermodell konnte weiterhin gezeigt werden, dass Glutathionmangel zur Apoptoseinduktion in der Netzhaut führt [45].…”
Section: Glutathion N-acetylcysteinunclassified